Private finance initiative in the United Kingdom - Ismail, Suhaiza (Lambert Academic Publishing, 2011)
The Private Finance Initiative (PFI) has become a widely used mechanism for delivering public services in the UK. The crucial requirements for entering into a PFI scheme are that the scheme must offer better value for money (VFM) than conventional procurement and be affordable. Since it was first introduced in 1992, there has been much controversy surrounding PFI. This study attempts to contribute to the debate over the benefits and costs of the scheme. Particularly, the study considered the extent to which VFM and affordability are actually demonstrated by the existing PFI projects and the performance of the PFI private sector providers. The study also recognised several other PFI issues such as the transfer of risks and the credibility of the public sector comparator (PSC) which are crucial to the assessment of VFM. The study consists of four parts. The first two parts analysed the extant literature on the performance of PFI projects. The first part looked at the audit reports by the official audit bodies, while the second part examined the published research carried out by non-audit organisations and individual researchers. Part three examined the profitability of several private sector companies which are heavily involved in the PFI projects. In response to calls for review of the fully operational PFI projects, the final part provided further evidence on VFM and affordability based on the results of a survey of the perceptions of users of PFI facilities and services in schools. The review of previous research revealed mixed evidence about the performance of PFI projects. There was evidence of both good and poor VFM delivered by the projects. The analysis of the performance of private sector companies suggested that no clear evidence of excessive profits were made by the companies from their PFI involvement. The results from the survey demonstrated that the majority of users were satisfied with the quality of the PFI facilities and services provided in their schools, and clearly felt that the PFI facilities provided were better than the pre-PFI facilities. The survey also suggested that there was little consensus in the perceptions about the VFM achieved from the PFI schemes. There was also mixed evidence concerning the issue of affordability. Overall, the study concluded that there was inconclusive evidence about the performance of PFI schemes. However, due to the long term nature of PFI contracts,it might be still too early to measure the true success of the PFI.